A Case of Chronic Graft-versus-Host-Disease Following Allogeneic Peripheral Blood Stem Cell Rescue for Poor Graft Function after Bone Marrow Transplantation - Kim, Hyeoung Joon (Korean J Intern Med, 1998)
To overcome poor graft function after allogeneic bone marrow transplantation (BMT), the use of peripheral blood stem cells (PBSC) instead of bone marrow is gaining more popularity because of its advantages. There may, however, be an increased risk of graft-versus-host-disease (GVHD) because of the large number of lymphocytes present in a leukapheresis product. An 18-year-old man with severe aplastic anemia underwent an allogeneic BMT using his HLA-identical sister. After initial excellent graft take for 8 months, his blood counts gradually decreased to 2.8 × 10(9)/L of white cells and 28 × 10(9)/L of platelets with marrow cellularity of <10%. After allogeneic granulocyte-colony stimulating factor mobilized PBSC rescue, the patient’s blood counts recovered satisfactorily. Around 1 year after the boost, he developed chronic GVHD that responded to prednisolone and cyclosporin A. He is now well on low-dose steroids at day +1055 after PBSC rescue. The present case is the first experience of a long-term follow-up who underwent allogeneic PBSC rescue in Korea.